Front Matter - JTSiskom Volume 6 Nomor 2 Tahun 2018 - JTSiskom, Editor in Chief (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2018)
This article contains front-matter of JTSiskom Volume 6 Number 2 Year 2018, which includes cover page, title page, editorial team, acknowledgment, editorial policy and table of contents. JTSiskom's editorial policies include focus and scope, review process statement, publication frequency, open access policy, archiving policy and statement of article processing fee.